Donor-Site Morbidity Following Radial Forearm Free Flap Harvest for Head and Neck Reconstruction: A Systematic Review and Meta-Analysis - Fabio Maglitto; Giovanni Salzano; Eutilia Manzo; Serena Trotta; Luigi Angelo Vaira; Marzia Petrocelli; Stefania Troise; Giovanni Dell’Aversana Orabona (Journal of Clinical Medicine, 2026)
Background: The radial forearm free flap (RFFF) remains one of the most reliable and widely adopted reconstructive options for head and neck defects because of its consistent vascular anatomy, long pedicle, and excellent tissue pliability. Nevertheless, donor-site morbidity continues to represent its principal drawback and may negatively affect postoperative recovery, upper-limb function, and patient satisfaction. Although numerous surgical modifications and donor-site reconstruction techniques have been proposed to reduce morbidity, the available evidence remains fragmented and heterogeneous. This systematic review and meta-analysis aimed to quantify the incidence of the principal donor-site complications following RFFF harvest and critically evaluate the current evidence regarding strategies to minimize donor-site morbidity. Methods: This systematic review and meta-analysis was conducted according to the PRISMA 2020 statement and prospectively registered in PROSPERO (CRD420261423543). PubMed/MEDLINE, Embase, and Scopus were systematically searched from inception to June 2026. Clinical studies reporting donor-site outcomes after RFFF harvest for head and neck reconstruction were eligible. Primary outcomes were tendon exposure and skin graft loss/failure. Random-effects meta-analyses were performed to estimate pooled incidence rates. Secondary complications, functional outcomes, and patient-reported outcome measures were synthesized qualitatively. Methodological quality and certainty of evidence were assessed using the Joanna Briggs Institute critical appraisal tools and the GRADE framework. Results: Twenty-two studies met the inclusion criteria for qualitative synthesis. Fourteen studies were included in the meta-analysis of tendon exposure and twelve in the meta-analysis of graft loss/failure. The pooled incidence of tendon exposure was 8% (95% CI, 7–11%; I2 = 0%), whereas the pooled incidence of graft loss/failure was 11% (95% CI, 7–16%; I2 = 67.1%). Delayed wound healing, infection, sensory disturbances, scar-related morbidity, and functional impairment were reported inconsistently across studies, precluding quantitative synthesis. Available studies generally reported limited long-term functional impairment, although substantial heterogeneity in assessment methods and follow-up precluded quantitative synthesis. Overall certainty of evidence was rated as low. Conclusions: Donor-site morbidity following RFFF harvest remains clinically relevant despite the excellent reconstructive reliability of the flap. Approximately one in twelve patients experiences tendon exposure and one in ten experiences graft loss or failure. Current evidence does not support the superiority of any specific donor-site reconstruction technique. Future high-quality prospective comparative studies adopting standardized outcome definitions and validated patient-reported measures are required to optimize donor-site management and improve reconstructive decision-making.